Problem-based Web-based Teaching in a Computational Linguistics Curriculum - Carstensen, Kai-Uwe; Hess, Michael (Linguistik Online, 2003)
This paper presents an approach for combining web-based learning (WBL) with problem-based learning (PBL), aiming at computer aided learning (CAL) support for introductory lectures to Computational Linguistics. Contrary to most current learning paradigms, we neither follow the "platform + content"-approach of current learning management systems used for distance learning, nor focus on the collaborative aspects of PBL. Instead we propose a text-centred concept for individual learning featuring problem-based interactive learning applications (TIP).